THE EFFECTIVENESS OF SIMULATION TRAINING ON BASIC RESUSCITATION MEASURES IN SKILLS TRAINING CENTER OF AVICENNA TAJIK STATE MEDICAL UNIVERSITY - N.G. RAKHIMOV; D.N. USMANOV; V.I. CHISTYAK; G.S. KAYUMOVA; KH. A. SAFOEV (Паёми Сино, 2017)
Objective: To study the effectiveness of simulation training for mastering basic life support by students of the 6th course of the Medical University.